Content Analysis of the Effects of Domestic Violence on Child Victims in the Movie Precious - Sijaya, Zaynab Army; Purwanti, Silviana; Agustian, Jaka Farih; Dwivayani, Kadek Dristiana (Jurnal Indonesia Sosial Sains, 2024)
Domestic violence is a dynamic phenomenon that can occur in all walks of life. Given the role of film as a tool to convey ideas and influence the audience, research on the effects of domestic violence in the movie Precious is interesting to do. The rampant news about domestic violence makes this research relevant because this movie can provide an overview of the destructive impact of domestic violence on children as victims. The aim of this research is to find out what the physical, psychological, sexual, and social effects are due to domestic violence experienced by the main character in the film Precious. This research uses a quantitative content analysis method with a descriptive approach. Data will be measured using a measurement table. The research population is the movie Precious with a duration of 1 hour 50 minutes, with a sample of scenes containing the effects of domestic violence. The results showed that Precious depicts various effects of domestic violence, such as loss of self-confidence, anxiety, lack of attention from parents, withdrawal from the family, use of harsh words, stress, depression, self-isolation, not given living expenses, embarrassment to meet others, problematic education, trauma, pregnancy, children replacing parental roles, loss of jobs, imagining the violence experienced, bruises, bumps on the body, and injuries.